2017
DOI: 10.1007/s00134-017-4858-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, multicenter trial of lateral Trendelenburg versus semirecumbent body position for the prevention of ventilator-associated pneumonia

Abstract: NCT01138540.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…Some investigators have hypothesized that putting patients in the lateral Trendelenburg may be a better way to prevent VAP by recruiting gravity to carry oral secretions away from the lungs. A recent study confirmed this hypothesis, but the trial was terminated early due to a surfeit of adverse events among patients randomized to lateral Trendelenburg [117].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…Some investigators have hypothesized that putting patients in the lateral Trendelenburg may be a better way to prevent VAP by recruiting gravity to carry oral secretions away from the lungs. A recent study confirmed this hypothesis, but the trial was terminated early due to a surfeit of adverse events among patients randomized to lateral Trendelenburg [117].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…Positioning the patient with the head of the bed elevated > 30° reduces aspiration and clinically confirmed VAP [15], but quality of evidence supporting this intervention is poor, and the optimal angulation of the head of the bed is still uncertain. The Gravity-VAP trial showed that the lateral-Trendelenburg position (LTP) could further reduce VAP, specifically in patients with healthy lungs upon intubation, but LTP feasibility appeared challenging [16]. To date, only ETTs comprising aspiration of subglottic secretions [17] reduced VAP by more than 50%, but substantial benefits were mostly corroborated in cardiac surgery patients.…”
Section: Non-pharmacological Measuresmentioning
confidence: 99%
“…Kombine grupta diğer 2 deney grubundan daha düşük oranda VİP görülmesi nedeniyle subglottik salgı drenajı ve semirekümbent pozisyon kombinasyonu VİP insidansını azaltabileceği saptanmıştır (19). Bassi ve arkadaşları (2017) tarafından yürütülen çalışmada VİP insidansı semirekümbent pozisyona kıyasla yan trendelenburg pozisyonunda daha düşük bulunmuştur (77). Wang ve arkadaşları (2014) gerçekleştirdikleri çalışma sonucunda gastrik motilite uyarıcı madde uygulaması ve hastalara semirekümbent pozisyon verilmesi , VİP' in önlenmesinde etkili olduğunu saptamışlardır (55).…”
Section: çAlışmalardan Elde Edilen Bulgularunclassified